Trait affectivity and response styles to positive affect: Negative affectivity relates to dampening and positive affectivity relates to enhancing. (July 2016) - Nelis, Sabine; Bastin, Margot; Raes, Filip; Mezulis, Amy; Bijttebier, Patricia
Abstract: Although there is ample research linking trait affect with response styles for negative affect, research on the link between trait affect and response styles for positive affect is scarce. The first aim of this study was to examine whether trait positive affect (trait PA) and trait negative affect (trait NA) predict cognitive response styles for positive affect. The second aim of this study was to examine whether such associations may be unidirectional or bidirectional. In three separate longitudinal datasets ( N  = 371, N  = 1552, N  = 183), we assessed trait PA, trait NA, dampening, and enhancing and examined cross-sectional and prospective relations among these constructs in children and young adolescents. Cross-sectionally, we found a robust relation between trait NA and dampening, whereas trait PA was unrelated to dampening. In terms of directionality, higher trait NA predicted more subsequent dampening in two of the three samples. For trait PA and enhancing, the longitudinal results pointed to a reciprocal positive relationship. The results support models of trait affect as a predictor of cognitive response styles to affect and extended these models by showing that a reciprocal relationship from the response style (i.e., enhancing) to trait affect should also be considered. Highlights: The study included three longitudinal samples of children and adolescents. We examined bidirectional relations between trait PA, NA, dampening, and enhancing. Trait PA predicted enhancing, not dampening. A reciprocal relationship from enhancing to trait PA was also found. Trait NA was associated with dampening.